2021
DOI: 10.1123/iscj.2020-0006
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Value Created in a Social Learning Space Intervention: Four Vignettes of Parasport Coaches

Abstract: In this paper, the authors reflect on the current literature and the evolution of coach communities of practice and how the coach development area has embraced Wenger-Trayner’s social learning theory. Studies examining parasport coach development interventions, specifically those using a landscape of practice approach, are lacking. This paper is the third in a series about increasing learning capability in the wheelchair curling landscape. The authors utilized a collaborative approach to assess the learning va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…In the literature, community-based learning studies are recommended in order to enhance coaches' capacity to apply their knowledge and methods ( 55 , 56 ). Collaborative learning environments designed based on this learning theory are known to be effective in providing quality learning environments for coaches [e.g., ( 58 60 )].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, community-based learning studies are recommended in order to enhance coaches' capacity to apply their knowledge and methods ( 55 , 56 ). Collaborative learning environments designed based on this learning theory are known to be effective in providing quality learning environments for coaches [e.g., ( 58 60 )].…”
Section: Discussionmentioning
confidence: 99%
“…To improve coaches’ capacity to apply knowledge in the areas the present study findings addressed, community-based learning research has been suggested in the literature ( Gilbert et al, 2009 ; Trudel et al, 2013 ). Such collaborative learning environments designed based on the social theory of learning (communities of practice; Wenger, 1998 ) have been evidenced as effective in providing quality learning environments for coaches (e.g., Culver and Trudel, 2006 ; Stoszkowski and Collins, 2014 ; Duarte et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Estratégias ao ensino e desenvolvimento de práticas reflexivas são apresentadas pelos autores, tais quais a utilização da aprendizagem baseada em A reflexão na formação inicial de treinadores esportivos: considerações para contextos de estágios 09 problemas (PBL), a reflexão em incidentes críticos, intervenções de reflexão baseadas em campo, trabalho com mentores e facilitação da reflexão com acesso à pares (GILBERT;TRUDEL, 2006). A literatura tem apresentado avanços como iniciativas de aprendizagem por meio da reflexão com facilitadores como coach developers, mentores, comunidades de prática e espaços sociais de aprendizagem (BERTRAM; CULVER; DUARTE;BOYD, 2019;RODRIGUES et al, 2020;WERTHNER, 2013;LEWIS, 2021). Entretanto, o presente ensaio irá considerar a aprendizagem daqueles que ainda se encontram na formação inicial.…”
Section: Individualunclassified